(untitled) (Contextos: Estudios de Humanidades y Ciencias Sociales, 2017)
at the university to students of vulnerable contexts, guarantying a vacancy for them in further education studies. To achieve this purpose, it is postulated that the work of the executioners relies on the teacher’s role as an agent of change. The accompaniment of the teachers has allowed us to learn about the reality of local education, through their difficulties, wealth and challenges of those who have opened their doors to us to observe the classes, in order to support them and carry out a reflexive process of their teaching practice, all of which has been done in order to improve the quality of education, especially in secondary education. The experience that we want to present is a theoretical basis to generate new competencies in teachers as reflexive experts of their work and to address technical difficulties and improve their teaching tools.